2013
DOI: 10.1039/c3ra22693j
|View full text |Cite
|
Sign up to set email alerts
|

Blood triggered rapid release porous nanocapsules

Abstract: Rapid-release drug delivery systems present a new paradigm in emergency care treatments. Such systems combine a long shelf life with the ability to provide a significant dose of the drug to the bloodstream in the shortest period of time. Until now, development of delivery formulations has concentrated on slow release systems to ensure a steady concentration of the drug. To address the need for quick release system, we created hollow polyacrylate nanocapsules with nanometer-thin porous walls. Burst release occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…32 Our spectroscopy study showed that it is not the case. An addition of serum to a free HITC dye leads to a substantial bathochromic shift (10 nm) (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…32 Our spectroscopy study showed that it is not the case. An addition of serum to a free HITC dye leads to a substantial bathochromic shift (10 nm) (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Similarly, encapsulation of fluorophores in micelles, liposomes, or polymeric nanoparticles affects their lifetime and, hence, their anisotropy. 53 Ionic strength does not directly affect the FA. However, very high affinity interactions (low-nM) are problematic for FA assays because they require the use of very low fluorophore concentrations, resulting in weak fluorescent signal.…”
Section: Steady-state Fluorescence Anisotropymentioning
confidence: 98%
“…Similarly, FA has validated the attachment of nanoparticles to fluorophore labeled DNA. 90 Gustafson et al 53 used FA to validate the encapsulation of an NIR imaging agent into porous nanocapsules designed for blood-triggered rapid release of cargo in emergency applications.…”
Section: Novel Applications: Biologics Nanotechnology and Imaginmentioning
confidence: 99%
“…Recently, we created NCs capable of burst release of encapsulated content upon contact with blood [84]. Rapid release is achieved by the expansion of intrinsic nanopores in the NC shell caused by the conformational change due to interactions with albumin.…”
Section: Biomedical Applications Of Polymer Nanocapsulesmentioning
confidence: 99%